2018
DOI: 10.1371/journal.pone.0195667
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen microbubbles improve radiotherapy tumor control in a rat fibrosarcoma model – A preliminary study

Abstract: Cancer affects 39.6% of Americans at some point during their lifetime. Solid tumor microenvironments are characterized by a disorganized, leaky vasculature that promotes regions of low oxygenation (hypoxia). Tumor hypoxia is a key predictor of poor treatment outcome for all radiotherapy (RT), chemotherapy and surgery procedures, and is a hallmark of metastatic potential. In particular, the radiation therapy dose needed to achieve the same tumor control probability in hypoxic tissue as in normoxic tissue can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 54 publications
(44 reference statements)
0
28
0
Order By: Relevance
“…Forty-two eight-week-old female Fischer 344 rats from Charles River Labs and rat fibrosarcoma tumor allografts were used [23]. The rat fibrosarcoma (FSA) allograft model has been well characterized in several radiotherapy response studies by our and collaborator labs [23][24][25]. Rat FSA is characterized as a local, non-metastasizing tumor that is highly vascular and oxygen dependent.…”
Section: Plos Onementioning
confidence: 99%
“…Forty-two eight-week-old female Fischer 344 rats from Charles River Labs and rat fibrosarcoma tumor allografts were used [23]. The rat fibrosarcoma (FSA) allograft model has been well characterized in several radiotherapy response studies by our and collaborator labs [23][24][25]. Rat FSA is characterized as a local, non-metastasizing tumor that is highly vascular and oxygen dependent.…”
Section: Plos Onementioning
confidence: 99%
“…UCA cavitation for localized delivery of gases, specifically oxygen, is less studied but represents a potentially viable delivery platform. Groups have proposed using nano‐ and micro‐sized UCAs stabilized with chitosan, dextran, protein, and lipid‐based shells to deliver oxygen …”
mentioning
confidence: 99%
“…On the topic of oxygen delivery for radiotherapy, Fix et al has previously shown that a 30% increase in tumoral hemoglobin saturation is sufficient to achieve a ~30% reduction in tumor growth rate by injection of ~3×10 10 OMBs/kg directly into the tumor [29]. For intravenous, as opposed to intratumoral administration, we see a constraint on OMB concentration (<5×10 8 OMB/mL) due to handling considerations related to excessive viscosity at high OMB concentrations.…”
Section: Discussionmentioning
confidence: 85%
“…In 2016, Owen et al showed that orally administered OMB can reduce tumor hypoxia [3]. In 2018, Fix et al showed that intra-tumoral injection lipid-coated OMB Ivyspring International Publisher can increase tumor oxygen levels and tumor control in a fibrosarcoma rat model [4]. In the same year, Eisenbrey et al showed that intravenous injection of surfactant-coated OMB can increase tumor oxygen and control in a breast cancer model [5,6].…”
Section: Introductionmentioning
confidence: 99%